2010
DOI: 10.1007/s00159-010-0034-0
|View full text |Cite
|
Sign up to set email alerts
|

Halo streams in the solar neighborhood

Abstract: The phase-space structure of our Galaxy holds the key to understand and reconstruct its formation. The CDM model predicts a richly structured phase-space distribution of dark matter and (halo) stars, consisting of streams of particles torn from their progenitors during the process of hierarchical merging. While such streams quickly loose their spatial coherence in the process of phase mixing, the individual stars keep their common origin imprinted into their kinematic and chemical properties, allowing the reco… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
36
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 114 publications
1
36
0
Order By: Relevance
“…Evidence of spatial and kinematical substructures in the Galactic halo resulting from this process has indeed been found as reviewed by Helmi (2008) and Klement (2010). Elemental abundance ratios of halo stars may also be used to probe this formation process by so-called "chemical tagging" of the "building blocks" (Freeman & Bland-Hawthorn 2002).…”
Section: Introductionmentioning
confidence: 92%
“…Evidence of spatial and kinematical substructures in the Galactic halo resulting from this process has indeed been found as reviewed by Helmi (2008) and Klement (2010). Elemental abundance ratios of halo stars may also be used to probe this formation process by so-called "chemical tagging" of the "building blocks" (Freeman & Bland-Hawthorn 2002).…”
Section: Introductionmentioning
confidence: 92%
“…Numerous studies in the last 15 yr have suggested that the imprints of past merger events, even if dispersed in configuration space, can still be identified in kinematics-related spaces, such as the energy-angular momentum space (hereafter referred to as E − L z , L z being the z component of the angular momentum for an axisymmetric potential where z is the symmetry axis), the L ⊥ − L z space, where L ⊥ is the angular momentum component in the x − y plane, or spaces of orbital parameters, such as the apocenter-pericenter-angular momentum space (APL) and its projections (Helmi et al 1999(Helmi et al , 2006Helmi & de Zeeuw 2000;Knebe et al 2005;Brown et al 2005;Font et al 2006;Choi et al 2007;Morrison et al 2009;Re Fiorentin et al 2015) -see also Klement (2010), Smith (2016) for two recent and comprehensive reviews.…”
Section: Introductionmentioning
confidence: 99%
“…More attention has been given to the study of the impact of AM redistribution in major mergers than in minor mergers (with mass ratios ≤0.1). This despite the fact that minor mergers are expected to be much more common than major mergers (Fakhouri & Ma 2008) and that many traces of ongoing or past interactions are visible both in the Milky Way (see Klement 2010, for a recent review), our neighbor galaxy Andromeda (Ibata et al 2001;McConnachie et al 2009) and other galaxies in the local Universe (Martinez-Delgado et al 2010). Di pointed out that the AM redistribution during minor mergers also have an impact on the kinematics of stellar disks and may explain the distribution of the orbital eccentricities of stars in the solar neighborhood.…”
Section: Introductionmentioning
confidence: 99%